دور مواقع التواصل الاجتماعي في العمل الدعوي الفيس بوك أنموذجا د ا رسة ميدانية بولاية الوادي - بن خميفة, إلهام; بن عمي, إيمان; عباسي, رئيفة (جامعة الوادي university of eloued, 2015)
تهدف هذه الد ا رسة إلى الكشفف نفد د ر ق فل الت اافج ااعتقفانف سالوف" يف س فف العقج الدن ي، قد خلاج د ا رسة ن"نة قد قسفتخدقف ق فل سالوف" يف س فف الف ادي، ل فد تف الانتقفاد نأفى سداي اسفتي"اد لعقفل الي"انفا ، س"فة تف ت سف" الاسفتقاري إلفى ففلاة قسفا ر القس ر الأ ج )معلومات أوليةة، القسف ر ال فانف )مسةوو الواالةو واتسةوخدال اليخ ة القسف ر ال الفة )مةد وة ير ،) Face book لموقةا الووا ةو اتعومةال الاةي ةو الاي و ف العمو الدلوي،. د ت اأ الد ا رسة إلى قعق نة قد النتائج. Abstract: This study aims to reveal the role of social networking "Facebook" sites in advocacy work , Through a sample study of users of the site "Facebook" in Oued souf City, We've been relying on a questionnaire for data collection , Where the questionnaire was divided into three axes : The first axis : (preliminary information) , the second axis: (level of interaction and personal use of social networking site "Facebook"), and the third axis: (over the Facebook effect in advocacy work) . The study found a range of results.
دعوة